Correction to: Aquaponic trends, configurations, operational parameters, and microbial dynamics: a concise review (Environment, Development and Sustainability, (2023), 27, 1, (213-246), 10.1007/s10668-023-03924-4) - Kushwaha J.; Priyadarsini M.; Rani J.; Pandey K.P.; Dhoble A.S. (My University, 2025)
In the original publication of the article, author has missed to add acknowledgement text and Credit line “Created with BioRender.com.” In both Fig. 3 and Fig. 4. The correct figure caption with credit lines are: Figure 3 Different aquaponics configurations a pilot-scale, b decoupled, c coupled, d multi-loop, e small-scale (Created with BioRender.com.) Figure 4 High-throughput techniques for examining microbial diversity in aquaponics (Created with BioRender.com.) Acknowledgment: The figures 3 and 4 presented in this manuscript were created using BioRender.com © The Author(s), under exclusive licence to Springer Nature B.V. 2024.